AN INVESTIGATION OF OUTCOME EXPECTANCIES AS A PREDICTOR OF TREATMENT RESPONSE FOR COMBAT VETERANS WITH PTSD: COMPARISON OF CLINICIAN, SELF‐REPORT, AND BIOLOGICAL MEASURES. Issue 6 (19th February 2015) - Price, Matthew; Maples, Jessica L.; Jovanovic, Tanja; Norrholm, Seth D.; Heekin, Mary; Rothbaum, Barbara O.
<x xml:space="preserve">Abstract</x> Background Outcome expectancy, or the degree to which a client believes that therapy will result in improvement, is related to improved treatment outcomes for multiple disorders. There is a paucity of research investigating this relation in regards to posttraumatic stress disorder (PTSD). Additionally, the bulk of the research on outcome expectancy and treatment outcomes has relied mostly on self‐report outcome measures. Methods The relation between outcome expectancy on self‐report measures, clinician‐rated measures, and two biological indices (fear‐potentiated startle and cortisol reactivity) of PTSD symptoms was explored. The sample included combat veterans (N = 116) treated with virtual reality exposure therapy for PTSD. Results Results supported a negative association between outcome expectancy and both self‐report and clinician‐rated symptoms at the conclusion of treatment, but outcome expectancy was related to the magnitude of change during treatment for self‐report measures only. Outcome expectancy was unrelated to biological measures of treatment response. Conclusions These findings suggest that outcome expectancy may be related to patient and clinician perceptions of outcomes, but not biological indices of outcome for PTSD.